Curcumin-Nucleotide Interaction by FT-Raman Spectroscopy - SENTHIL, K.; IYANDURAI, N.; SAROJINI, R. (Asian Journal of Chemistry, 2010)
The interaction of deoxyguanosine-5′-monophosphate (dGMP) with curcumin is investigated in aqueous solution at physiological pH with drug/dGMP (phosphate) molar ratios of r = 1/50, 1/20, 1/10 and 1/5. Fourier Transform Raman (FT Raman) spectroscopy is used to determine drug binding sites, dGMP secondary structure, as well as the structural variations of curcumin-dGMP complexes in aqueous solution. Spectroscopic evidence showed that at low curcumin concentration (1/50), drugdGMP interaction is mainly through the backbone PO2 groups. Such interaction largely perturbs the phosphate vibration near 1053 cm-1. At higher drug concentration (r >1/10) the participation of guanine base in drug-dGMP complexation was evidenced by strong perturbations of guanine vibrations near 1717 cm-1.